Analisis Pengaruh Sektor Pertanian Terhadap Pertumbuhan Ekonomi Desa Sidoharjo dalam Perspektif Ekonomi Islam - Mahdalena Mahdalena; Afif Arrosyid; Sri Rahayu Ningsih (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This examination means to break down the impact of the farming area on the monetary development of Sidoharjo town from an Islamic financial viewpoint. In this examination the creator utilizes a quantitative exploration approach. According to its temperament, this exploration is elucidating investigation. The examination populace taken was the whole local area of Sidoharjo Town. The technique utilized in gathering test information for this exploration was purposive examining. The information assortment methods utilized were perception, documentation, polls and meetings. In view of the examination of the farming area on the monetary development of Sidoharjo Town, it tends to be seen from the coefficient of assurance of the cost variable r table. In light of the examination results, the r table worth is 0.000. Consequently, it shows that the examination of the horticultural area on financial development has a huge positive impact. One of the standards of financial improvement according to an Islamic viewpoint. Islam helps us to use normal assets as per the orders of Allah SWT, specifically by securing and really focusing on assets well, not obliterating existing assets, and having the option to use the economy of a district. This is demonstrated in the rural area, particularly in South Lampung Rule, the agrarian area is exceptionally advantageous for the economy, specifically it can give amazing chances to work creation, work on the wheels of the economy and impact the advancement of the business world. . so it can diminish joblessness with countless specialists from the farming area.